Zwitterionic polymer hydrogel as well as preparation method and application thereof

The zwitterionic polymer hydrogel prepared by one pot method combines the polymerization of SBMA, THMA and AM to solve the problem that both conductivity and mechanical properties cannot be combined, and high conductivity and excellent adhesion and mechanical properties are achieved. It is suitable for the preparation of flexible biosensors and wound monitoring.

CN119505084AActive Publication Date: 2025-02-25SHAANXI UNIV OF SCI & TECH

Patent Information

Application Number
CN202411683047.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-25
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

In the prior art, both conductive and mechanical properties cannot be achieved, and traditional wound dressings lack real-time monitoring capabilities, which limits the diagnosis and treatment of medical staff.

Method used

Zwitterionic polymer hydrogels were prepared by a one-pot method, and hydrogels with excellent adhesion and mechanical properties were formed by radical polymerization of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonate propyl)ammonium hydroxide (SBMA), N-[tris(hydroxymethyl)methacrylamide (THMA) and acrylamide (AM) under initiator and crosslinking agent.

Benefits of technology

It has achieved high conductivity and good mechanical properties of zwitterionic polymer hydrogels, and is suitable for the preparation of flexible biosensors, and has broad application prospects for healthcare management and wound monitoring.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505084A_ABST
    Figure CN119505084A_ABST
Patent Text Reader

Abstract

The invention discloses zwitterionic polymer hydrogel as well as a preparation method and application thereof. The preparation method comprises the following steps: dissolving THMA in water, stirring and dispersing to form THMA suspension; adding AM, SBMA, an initiator and a cross-linking agent into the THMA suspension, and uniformly stirring to prepare a precursor liquid; according to the method, the process is simple, the design is reasonable, the polymer hydrogel with both mechanical performance and conductivity is obtained, the double-attack promotion effect of the hydrogel on promoting wound healing and synchronously monitoring the wound healing condition in real time is achieved, and the application prospect is wide. Wide application prospects are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of intelligent monitoring sensors and relates to a zwitterionic polymer hydrogel and a preparation method and application thereof. Background Art

[0002] Conductive hydrogel is a water-rich material that can mimic the softness of human tissue and provide the necessary moist environment for wound healing. This type of hydrogel can absorb tissue exudate, allow oxygen to penetrate and cool the wound, thereby alleviating the patient's pain. Effective medical dressings need to have good conductivity, adhesion and biocompatibility to ensure signal accuracy and patient safety. Among various hydrogels, zwitterionic hydrogels have attracted widespread attention due to their conductivity, low cost and easy preparation. This type of hydrogel contains both cationic and anionic groups, which can enhance conductivity by promoting the movement of ions along the polymer backbone. Existing studies usually increase the conductivity of sensors by adding conductive materials, but this may affect the mechanical properties and adhesion of hydrogels. In addition, wound healing is a complex and dynamic physiological and biochemical process. However, traditional wound dressings (such as gauze, bandages, cotton cloth, etc.) have obvious shortcomings. For example, patents CN202210080243.5 and CN201720686560.6 disclose non-woven wound dressings and their applications and wound dressings, respectively. While supporting wound healing, these dressings cannot effectively maintain a moist environment and elasticity, and lack real-time monitoring capabilities, which limits the diagnosis and treatment of medical staff and increases the burden on patients. Summary of the invention

[0003] In view of the problems existing in the prior art, the present invention provides a zwitterionic polymer hydrogel and a preparation method and application thereof, thereby solving the technical problem in the prior art that mechanical properties and conductive properties cannot be achieved at the same time.

[0004] The present invention is achieved through the following technical solutions: A method for preparing a zwitterionic polymer hydrogel comprises the following steps: S1: dissolving THMA in water and stirring to disperse to form a THMA suspension; S2: adding AM, SBMA, an initiator and a cross-linking agent to the THMA suspension, stirring evenly, to prepare a precursor liquid; S3: causing the precursor liquid to undergo a free radical polymerization reaction to obtain the zwitterionic polymer hydrogel.

[0005] Preferably, in step S1, the ratio of THMA to water is (40-90):300, calculated by mass fraction.

[0006] Preferably, in step S2, the molar ratio of the SBMA to the THMA is (1-9):(9-1).

[0007] Preferably, in step S2, the molar ratio of the SBMA to the THMA is 6:4.

[0008] Preferably, in step S2, the ratio of AM, SBMA, initiator and cross-linking agent is 20:(20-100):6:1, calculated by mass fraction.

[0009] Preferably, in step S2, the initiator is at least one of ammonium persulfate, potassium persulfate, azobisisobutylamidine hydrochloride, azobisisobutylimidazoline hydrochloride, azobiscyanovaleric acid and azobisisopropylimidazoline.

[0010] Preferably, in step S2, the cross-linking agent is at least one of polyethylene glycol diglycidyl ether, N,N'-methylenebisacrylamide, hydrazine peroxide, diallyl phthalate, divinylbenzene, diisocyanate, dicumyl peroxide, di-tert-butyl peroxide and styrene.

[0011] Preferably, in step S3, the temperature of the free radical polymerization reaction is 30-100° C., and the time is 2-10 hours.

[0012] A zwitterionic polymer hydrogel is prepared by the above method; the conductivity of the hydrogel is 0.72-1.58 S / m.

[0013] The above-mentioned zwitterionic polymer hydrogel is used in the preparation of flexible biosensors.

[0014] Compared with the prior art, the present invention has the following beneficial technical effects: The invention discloses a method for preparing a zwitterionic polymer hydrogel. The method adopts a one-pot method to polymerize reactive monomers [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonatepropyl)ammonium hydroxide (SBMA), N-[tris(hydroxymethyl)methyl]acrylamide (THMA) and acrylamide (AM) in the presence of an initiator and a crosslinking agent by free radical polymerization, wherein the dipole-dipole interaction and non-covalent interaction between polymer chains can contribute to the bonding performance thereof, and the zwitterionic polymer hydrogel has good conductive properties. The flexible biosensor prepared by the zwitterionic polymer hydrogel has broad application prospects in medical care management and wound monitoring. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0016] Figure 1 A schematic diagram of a method for preparing a zwitterionic polymer hydrogel according to the present invention; Figure 2 The adhesion strength of zwitterionic polymer sensors prepared in different embodiments, wherein (a) is the adhesion performance test curve of STA hydrogel on different materials; (b) is the digital photo of the adhesion of STA hydrogel on different materials; (c) is the adhesion performance test curve of STA hydrogel on pig skin; Figure 3 Figures showing the mechanical properties of zwitterionic polymer hydrogels prepared in different embodiments, where (a) is the tensile curve of different STA hydrogels; (b) is the fracture strength and fracture strain of different STA hydrogels; Figure 4a The conductivity of STA hydrogels prepared in different embodiments; Figure 4b Using hydrogel as a cardiac patch to monitor human electrocardiogram; Figure 4c This is the electrocardiogram detail; Figure 5 (a) shows the electrical signal monitoring of mice on the third day of wound recovery, and (b) shows the electrical signal monitoring of mice on the seventh day of wound recovery; Figure 6 Zwitterionic hydrogel promotes wound healing. DETAILED DESCRIPTION

[0017] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0018] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0019] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0020] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0021] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0022] like Figure 1 As shown, the present invention provides a method for preparing a zwitterionic polymer hydrogel, comprising the following steps: S1: dissolving THMA in water, stirring and dispersing, and forming a THMA suspension; THMA has poor solubility in water, and after exceeding a certain solid content, the solid particles cannot be dissolved, and heating can accelerate its dissolution rate. Preferably, the heating temperature is 30-200°C; Wherein, in step S1, the ratio of THMA to water is (10-100):300, calculated by mass fraction.

[0023] S2: adding AM, SBMA, an initiator and a cross-linking agent to the THMA suspension, stirring evenly, to prepare a precursor liquid; Wherein, in step S2, the molar ratio of the SBMA to the THMA is (1-9):(9-1).

[0024] Preferably, the molar ratio of the SBMA to the THMA is 6:4.

[0025] In terms of mass fraction, in step S2, the ratio of AM, SBMA, initiator and cross-linking agent is 20:(20-150):6:1.

[0026] In step S2, the initiator is at least one of ammonium persulfate, potassium persulfate, azobisisobutylamidine hydrochloride, azobisisobutylimidazoline hydrochloride, azobiscyanovaleric acid and azobisisopropylimidazoline. The mass fraction of the initiator to the total mass of all monomers is 6%.

[0027] The crosslinking agent is at least one of polyethylene glycol diglycidyl ether, N,N'-methylenebisacrylamide, hydrazine peroxide, diallyl phthalate, divinylbenzene, diisocyanate, dicumyl peroxide, di-tert-butyl peroxide and styrene. The mass fraction of the crosslinking agent to the total mass of all monomers is 0.6%.

[0028] S3: causing the precursor liquid to undergo a free radical polymerization reaction to obtain the zwitterionic polymer hydrogel, which can be labeled as STA. The temperature of the free radical polymerization reaction is 30-200°C and the time is 2-10 hours. The structural formula of the obtained hydrogel is:

[0029] Among them, m, n, and g are all 400~6667.

[0030] The present invention also discloses a zwitterionic polymer hydrogel prepared by the above method, wherein the molecular weight of the hydrogel is 30,000 to 500,000, the conductivity of the hydrogel is 0.72 to 1.58 S / m, the adhesion strength is 13.1 to 14.5 KPa, and the tensile strength is 1400% to 1500%.

[0031] At the same time, the present invention also discloses the use of the above-mentioned zwitterionic polymer hydrogel in the preparation of a flexible biosensor. The flexible biosensor can realize integrated monitoring of patient diagnosis, treatment and rehabilitation.

[0032] The present invention adopts a one-pot method to free radical polymerize the reactive monomers [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonatepropyl)ammonium hydroxide (SBMA), N-[tris(hydroxymethyl)methyl]acrylamide (THMA) and acrylamide (AM) in the presence of an initiator and a crosslinker. The dipole-dipole interaction and non-covalent interaction between the polymer chains can contribute to their bonding properties. Flexible biosensors made of ion-conductive hydrogels have broad application prospects in healthcare management and wound monitoring.

[0033] The zwitterion [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonatepropyl)ammonium hydroxide (SBMA) selected in the present invention has a strong dipole property, and the association between its polymer chains provides physical crosslinking, thereby enhancing the mechanical properties of the hydrogel sensor. The reactive monomer N-[tris(hydroxymethyl)methyl]acrylamide (THMA) provides triple hydrogen bonding and load sharing effects, further improving the adhesion. By selecting SBMA, THMA and AM as reactive monomers and polyethylene glycol diglycidyl ether (PEGDE) as a crosslinker, the zwitterionic polymer hydrogel sensor prepared by a free radical polymerization method exhibits excellent adhesion and mechanical properties, successfully solving the problem of adhesion.

[0034] The material preparation process of the present invention is carried out under mild reaction conditions, without the need for high temperature and high pressure, and is safe, environmentally friendly, low-cost, and suitable for mass production. The prepared zwitterionic hydrogel has rapid gelation and high bonding strength, is suitable for wound bonding, hemostasis and repair, and is easy to use. The prepared sensor has good conductivity and flexibility. Based on the dipole-dipole interaction in zwitterionic polymers, the designed hydrogel smart sensor exhibits high sensitivity, rapid response and good stability, and can effectively monitor human diseases and recovery. Utilizing the phenomenon that wound inflammation causes local temperature increase, the highly sensitive hydrogel smart sensor can record electrical signals during wound healing, analyze temperature changes to determine the inflammation of the wound, and promote wound healing, realizing the integrated intelligent monitoring of human "diagnosis, treatment and recovery".

[0035] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0036] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0037] Example 1 First, 90 parts of N-[tris(hydroxymethyl)methyl]acrylamide (THMA) were added to 300 parts of deionized water, and a uniform THMA suspension A was obtained by magnetic stirring. Then, 20 parts of reactive monomer acrylamide (AM), 20 parts of SBMA (n SBMA :n THMA =1:9), 6 parts of initiator ammonium persulfate (APS) and 1 part of polyethylene glycol diglycidyl ether (PEGDE) were added to the THMA suspension A, and stirring was performed while adding the reagents to obtain a uniform precursor solution B; finally, the precursor solution B was transferred to a glass plate mold and reacted at 50°C for 4 h to obtain a zwitterionic polymer hydrogel with a molecular weight of 30,000 to 500,000 after free radical polymerization.

[0038] Example 2 First, 80 parts of N-[tris(hydroxymethyl)methyl]acrylamide (THMA) were added to 300 parts of deionized water, and a uniform THMA suspension A was obtained by magnetic stirring. Then, 20 parts of reactive monomer acrylamide (AM), 30 parts of SBMA (n SBMA :n THMA =2:8), 6 parts of initiator ammonium persulfate (APS) and 1 part of polyethylene glycol diglycidyl ether (PEGDE) were added to the THMA suspension A, and stirring was performed while adding the reagents to obtain a uniform precursor solution B; finally, the precursor solution B was transferred to a glass plate mold and reacted at 50°C for 4 h to obtain a zwitterionic polymer hydrogel with a molecular weight of 30,000 to 500,000 after free radical polymerization.

[0039] Example 3 First, 70 parts of N-[tris(hydroxymethyl)methyl]acrylamide (THMA) were added to 300 parts of deionized water, and a uniform THMA suspension A was obtained by magnetic stirring. Then, 20 parts of reactive monomer acrylamide (AM), 50 parts of SBMA (n SBMA :n THMA =3:7), 6 parts of initiator ammonium persulfate (APS) and 1 part of polyethylene glycol diglycidyl ether (PEGDE) were added to the THMA suspension A, and stirring was performed while adding the reagents to obtain a uniform precursor solution B; finally, the precursor solution B was transferred to a glass plate mold and reacted at 50°C for 5 h to obtain a zwitterionic polymer hydrogel with a molecular weight of 30,000 to 500,000 after free radical polymerization.

[0040] Example 4 First, 60 parts of N-[tris(hydroxymethyl)methyl]acrylamide (THMA) were added to 300 parts of deionized water, and a uniform THMA suspension A was obtained by magnetic stirring. Then, 20 parts of reactive monomer acrylamide (AM), 70 parts of SBMA (the molar ratio of SBMA:THMA was 4:6), 6 parts of initiator ammonium persulfate (APS) and 1 part of polyethylene glycol diglycidyl ether (PEGDE) were added to the THMA suspension A, and stirring was performed while adding the reagents to obtain a uniform precursor solution B. Finally, the precursor solution B was transferred to a glass plate mold and reacted at 50°C for 5 h to obtain a zwitterionic polymer hydrogel with a molecular weight of 30,000 to 500,000 after free radical polymerization.

[0041] Example 5 First, 50 parts of N-[tris(hydroxymethyl)methyl]acrylamide (THMA) were added to 300 parts of deionized water, and a uniform THMA suspension A was obtained by magnetic stirring. Then, 20 parts of reactive monomer acrylamide (AM), 80 parts of SBMA (nSBMA :n THMA =5:5), 6 parts of initiator ammonium persulfate (APS) and 1 part of polyethylene glycol diglycidyl ether (PEGDE) were added to the THMA suspension A, and stirring was performed while adding the reagents to obtain a uniform precursor solution B; finally, the precursor solution B was transferred to a glass plate mold and reacted at 50°C for 5 h to obtain a zwitterionic polymer hydrogel with a molecular weight of 30,000 to 500,000 after free radical polymerization.

[0042] Table 1 shows the performance test results of the hydrogels prepared in Examples 1 to 5 of the present invention, specifically: Table 1 Summary of performance of different samples

[0043] Figure 2 (a) is a graph showing the adhesion curves of the hydrogel prepared in the present invention on different substrates, namely, rubber, planks, paper, iron, and plastic; Figure 2 (b) is the adhesion diagram of the hydrogel prepared in the present invention on different substrates, including glass. As can be seen from the figure, the adhesion strength of STA hydrogel on rubber, wood, paper, iron sheet and plastic are 9.7, 16.3, 16.7, 28.0 and 35.7 KPa respectively; Figure 2 (c) is a test curve of the adhesion performance of different hydrogels prepared in the embodiments of the present invention on pig skin. It can be seen from the figure that the maximum adhesion force of the STA hydrogel prepared in the present invention on pig skin tissue is 13.5 Kpa. In summary, the STA hydrogel prepared in the present invention exhibits strong adhesion on the surfaces of various materials.

[0044] Figure 3 Figure 1 is a graph of the mechanical properties of zwitterionic polymer hydrogels of different embodiments. Mechanical toughness enables human tissues to perform motor functions and is an important factor in determining the biological functions of oligomeric hydrogels. Therefore, hydrogel biosensors must be flexible. Among them, (a) is the tensile curve of different STA hydrogels. It can be seen from the figure that with the increase of SBMA content, the fracture strength of the hydrogel shows an increasing trend; (b) is the fracture strength and fracture strain of different STA hydrogels. It can be seen from the figure that with the increase of SBMA content, the tensile strength gradually increases from 24 KPa to 46 KPa, and the fracture strain gradually increases from 368% to 1487%. The results show that the introduction of SBMA enhances the mechanical properties of STA hydrogels. This is attributed to the formation of polymer networks and the increase of non-covalent interactions in STA hydrogels.

[0045] Figure 4ais the electrical conductivity of STA hydrogel. It can be seen from the figure that PolySBMA polymer containing anionic and cationic groups has dipole-dipole interaction, which can promote the transmission of charged particles along the main chain, thereby improving the conductivity of the hydrogel. The impedance of STA hydrogel was measured by electrochemical impedance spectroscopy (EIS). The electrical conductivity of STA hydrogel is between 0.72 and 1.58 S / m.

[0046] Figure 4b The hydrogel is used as a heart patch to monitor the human electrocardiogram. As can be seen from the figure, when the STA hydrogel sensor is used to diagnose ECG signals, its accuracy and stability are highly similar to those of commercially available gel electrodes.

[0047] Figure 4c The figure shows the ECG detail. It can be seen that the ECG signal strength displayed by STA Z-hydrogel is 1.14 times that of the commercial gel electrode, and the signal response time is only 38.99 milliseconds, indicating that it has excellent signal response ability. Therefore, in addition to having good mechanical and adhesion properties, the hydrogel in the present invention also has good ionic conductivity in the case of inorganic salts.

[0048] Figure 5 The monitoring performance of the hydrogel on the wound site, (a) is the electrical signal monitoring of the mouse wound on the third day of recovery, (b) is the electrical signal monitoring of the mouse wound on the seventh day of recovery. It can be seen from the figure that on the third day, the relative change in resistance (ΔR / R0) between the wound site and the blank control group was 16.09±2.49%. On the seventh day, the relative change in resistance (ΔR / R0) between the wound group and the control group dropped to 2.33±0.73%. Therefore, STA Z-hydrogel can be used as a biosensor to successfully track wound healing by monitoring the temperature of the wound site.

[0049] Figure 6 The recovery of the wound when the zwitterionic hydrogel promotes wound healing, and the healing efficiency of STA hydrogel in the wound was understood through the mouse full-thickness skin defect model. The process of STA hydrogel treating wounds is detailed in the experimental section. As shown in the figure, on the 7th day, although the wounds of all groups showed re-epithelialization, the wound healing in the STA hydrogel group was significantly higher than that in the control group and the commercial Duoderm group. It is worth noting that on the 10th day, the tissue in the STA hydrogel group showed a significant state of contraction, while the control group still showed a large area of ​​scab. In addition, after 14 days of wound treatment, the wound closure rate in the STA hydrogel group reached almost 100%.

[0050] Example 6 A method for preparing a zwitterionic polymer hydrogel comprises the following steps: S1: dissolving THMA in water, stirring and dispersing, and forming a THMA suspension; THMA has poor solubility in water. When the solid content exceeds a certain value, the solid particles cannot be dissolved, and heating can accelerate the dissolution rate. Preferably, the heating temperature is 30° C.; wherein, in terms of mass fraction, the ratio of THMA to water is 100:300.

[0051] S2: Adding AM, SBMA, an initiator and a cross-linking agent to the THMA suspension, stirring evenly, to prepare a precursor liquid; wherein the molar ratio of the SBMA to the THMA is 1:9, and the ratio of the AM, SBMA, initiator and cross-linking agent is 20:20:6:1 in terms of mass fraction.

[0052] S3: causing the precursor liquid to undergo a free radical polymerization reaction to obtain the zwitterionic polymer hydrogel, which can be labeled as STA. The temperature of the free radical polymerization reaction is 30° C. and the time is 10 h.

[0053] Example 7 A method for preparing a zwitterionic polymer hydrogel comprises the following steps: S1: dissolving THMA in water, stirring and dispersing, and forming a THMA suspension; THMA has poor solubility in water. When the solid content exceeds a certain level, the solid particles cannot be dissolved, and heating can accelerate the dissolution rate. Preferably, the heating temperature is 200° C.; wherein, in terms of mass fraction, the ratio of THMA to water is 10:300.

[0054] S2: Adding AM, SBMA, an initiator and a cross-linking agent to the THMA suspension, stirring evenly, to prepare a precursor liquid; wherein the molar ratio of the SBMA to the THMA is 9:1, and the ratio of the AM, SBMA, initiator and cross-linking agent is 20:150:6:1 in terms of mass fraction.

[0055] S3: causing the precursor liquid to undergo a free radical polymerization reaction to obtain the zwitterionic polymer hydrogel, which can be labeled as STA. The temperature of the free radical polymerization reaction is 200° C. and the time is 2 hours.

[0056] Example 8 A method for preparing a zwitterionic polymer hydrogel comprises the following steps: S1: dissolving THMA in water, stirring and dispersing, and forming a THMA suspension; THMA has poor solubility in water. When the solid content exceeds a certain level, the solid particles cannot be dissolved, and heating can accelerate the dissolution rate. Preferably, the heating temperature is 100° C.; wherein, in terms of mass fraction, the ratio of THMA to water is 40:300.

[0057] S2: Adding AM, SBMA, an initiator and a cross-linking agent to the THMA suspension, stirring evenly, to prepare a precursor liquid; wherein the molar ratio of the SBMA to the THMA is 6:4, and the ratio of the AM, SBMA, initiator and cross-linking agent is 20:100:6:1 in terms of mass fraction.

[0058] S3: causing the precursor liquid to undergo a free radical polymerization reaction to obtain the zwitterionic polymer hydrogel, which can be labeled as STA. The temperature of the free radical polymerization reaction is 100° C. and the time is 5 hours.

[0059] The present invention synthesizes for the first time a preparation method of a "diagnosis and treatment" integrated intelligent sensor based on zwitterionic polymer hydrogel. Its advantage is that the introduction of N-[tris(hydroxymethyl)methyl]acrylamide (THMA) provides triple hydrogen bonds and load-sharing effects for the polymer hydrogel adhesive structure, thereby producing stronger adhesion; at the same time, [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl) ammonium hydroxide (SBMA) has strong dipole properties, and its interchain association can provide physical crosslinking to enhance the mechanical properties of the adhesive. At the same time, its dipole-dipole interaction can promote the transport of charged ions in the polymer, giving the hydrogel conductive properties. This hydrogel can not only promote wound healing, but also realize the integration of "diagnosis and treatment" monitoring by monitoring the changes in electrical signals caused by the temperature increase caused by the inflammatory phenomenon in wound healing.

[0060] The present invention is a method for preparing an integrated intelligent sensor for diagnosis and treatment based on zwitterionic polymer hydrogels. The method adopts a one-pot method to polymerize the reaction monomers [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonatepropyl)ammonium hydroxide (SBMA), N-[tris(hydroxymethyl)methyl]acrylamide (THMA) and acrylamide (AM) by free radical polymerization under the conditions of an initiator and a crosslinking agent. The present invention solves the problem that the existing conductive hydrogel sensors cannot have both adhesion and conductivity, and thus the sensors are widely used in the field of health monitoring.

[0061] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

[0062] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a zwitterionic polymer hydrogel, characterized in that: The following steps are involved: S1: dissolving THMA in water and stirring to disperse to form a THMA suspension; S2: adding AM, SBMA, initiator and cross-linking agent to the THMA suspension, stirring evenly to prepare a precursor liquid; S3: causing the precursor liquid to undergo a free radical polymerization reaction to obtain the zwitterionic polymer hydrogel.

2. The method for preparing a zwitterionic polymer hydrogel according to claim 1, characterized in that: In terms of mass fraction, in step S1, the ratio of THMA to water is (10-100):

300.

3. The method for preparing a zwitterionic polymer hydrogel according to claim 1, characterized in that: In step S2, the molar ratio of the SBMA to the THMA is (1-9):(9-1).

4. The method for preparing a zwitterionic polymer hydrogel according to claim 1, characterized in that: In step S2, the molar ratio of the SBMA to the THMA is 6:

4.

5. The method for preparing a zwitterionic polymer hydrogel according to claim 1, characterized in that: In terms of mass fraction, in step S2, the ratio of AM, SBMA, initiator and cross-linking agent is 20:(20-150):6:

1.

6. The method for preparing a zwitterionic polymer hydrogel according to claim 1, characterized in that: In step S2, the initiator is at least one of ammonium persulfate, potassium persulfate, azobisisobutylamidine hydrochloride, azobisisobutylimidazoline hydrochloride, azobiscyanovaleric acid and azobisisopropylimidazoline.

7. The method for preparing a zwitterionic polymer hydrogel according to claim 1, characterized in that: In step S2, the cross-linking agent is at least one of polyethylene glycol diglycidyl ether, N,N'-methylenebisacrylamide, hydrazine peroxide, diallyl phthalate, divinylbenzene, diisocyanate, dicumyl peroxide, di-tert-butyl peroxide and styrene.

8. The method for preparing a zwitterionic polymer hydrogel according to claim 1, characterized in that: In step S3, the temperature of the free radical polymerization reaction is 30-100° C. and the time is 2-10 hours.

9. A zwitterionic polymer hydrogel, characterized in that: Prepared by the method described in any one of claims 1 to 8; the conductivity of the hydrogel is 0.72 to 1.58 S / m, the adhesion strength is 13.1 to 14.5 KPa, and the tensile strength is 1400% to 1500%.

10. Use of the zwitterionic polymer hydrogel according to claim 9 in preparing a flexible biosensor.

Citation Information

Patent Citations

  • Non-woven fabric wound dressing, dressing bag and application thereof

    CN114366442A

  • Wound dressing

    CN208031378U

  • Preparation method of high-flexibility amphoteric ionic hydrogel

    CN105295073A

  • Preparation method of tough anti-freezing hydrogel with self-adhesion

    CN113292742A

  • Conductive polymer hydrogel sensing material with high elongation and strain sensitivity as well as preparation method and application of conductive polymer hydrogel sensing material

    CN114044920A

Cited By

  • Conductive hydrogel dressing, preparation method and application of conductive hydrogel dressing in electrically promoted healing

    CN119971133A